Dynamic environmental targets and technological progress - Dennis J. Snower (Fachverlag für Wirtschaft und Technik, 1980)
This paper analyzes socially optimal responses of environmental targets (i.e. targets on pollutant flows) to different types of technological progress. with reference to a simple macro-economic model including production, pollution generation, and pollution treatment, a socially optimal temporal sequence of environmental targets is derived. in this context, it is shown that different technological improvements (e.g. increases in labor productivity or improvements in the pollution technology of the production activity) require different dynamic target responses. moreover, every technological improvement representable by the model calls for a "intertemporal target reversal", i.e. a change in the environmental target's direction of movement through time.
Keywords: 330; Umweltschutz; Technischer Fortschritt; Gesamtwirtschaftliche Produktionstheorie